2022
DOI: 10.33059/jseb.v13i2.3342
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internal and External Factors on Non-Performing Financing at Islamic Commercial Banks in Indonesia

Abstract: The purpose of this study was to determine the effect of internal and external factors on non-performing financing in Islamic commercial banks and Islamic business units in Indonesia. Data is collected from publications of Bank Indonesia, the Central Statistics Agency, and the Financial Services Authority. Samples were taken from January 2010 to December 2017. Data were analyzed using Fisher’s exact test, Student's t-test, and multiple linear regression analysis. The results identify that Finance to Deposit Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…Research conducted by (Rahmah et al, 2021;Soekapdjo et al, 2019;Sugiyanto, 2020) stated that inflation does not impact the NPF. Contrary to the findings of (Amelia, 2019;Nasir et al, 2022) this shows that inflation has a negative and significant impact on nonperforming financing (NPF).…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Research conducted by (Rahmah et al, 2021;Soekapdjo et al, 2019;Sugiyanto, 2020) stated that inflation does not impact the NPF. Contrary to the findings of (Amelia, 2019;Nasir et al, 2022) this shows that inflation has a negative and significant impact on nonperforming financing (NPF).…”
Section: Introductioncontrasting
confidence: 99%
“…Research conducted by (Harahap & Alam, 2020;Rahmah et al, 2021;Soekapdjo et al, 2019;Sugiyanto, 2020) shows that inflation has no impact on NPF. In contrast, (Amelia, 2019;Nasir et al, 2022) found that the inflation variable had a negative and significant impact on NPF.…”
Section: Inflationmentioning
confidence: 81%
See 2 more Smart Citations
“…It is reinforced by Muyassaroh & Saputra's (2015) research, where FDR has a significant effect on PDM. H3: Financing to Deposit Ratio Affects Profit Distribution Management According to Nasir et al (2022), financing risk (non-performing financing) occurs due to financing failures caused by the inability of banks to recover the amount of financing or obtain returns on investments that have been disbursed. If this ratio continues to increase, the bank shows that the soundness of its financing is of poor quality.…”
Section: Hypothesismentioning
confidence: 99%